A271 UNCOVERING GENDER-BASED DIFFERENCES IN UNDIAGNOSED CELIAC DISEASE - Jansson-Knodell, C L (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Celiac disease affects numerous aspects of women’s health. There is a gap in research focused on gender-based differences in undiagnosed populations with celiac disease. AIMS: The aim of this study was to estimate gender-based differences in a unique population-based cohort of patients seropositive for celiac disease with respect to 1) age, 2) anthropomorphic measurements, and 3) associated diseases. METHODS: Stored serum from a population-based sample of 30,610 people in a Minnesota county was tested for celiac disease based on tissue transglutaminase (TTG) and endomysial antibody (EMA) positivity. Study subjects lived in Olmsted county, provided consent for waste blood testing and were aged 18–49 years old. Laboratory testing occurred between 6/2006 and 10/2009. Clinical data were systematically abstracted from the electronic medical record of a population-based undiagnosed cohort of patients who were seropositive for celiac disease defined as TTG and EMA positive testing. Categorical data were analyzed with Chi-square and Fisher’s exact test. Age was explored with the equal variance T-test. RESULTS: In this population-based cohort 281 (0.94%) subjects were identified with undiagnosed celiac disease. That group was comprised of 179 females and 102 males; the female to male ratio was 1.75:1. Seropositive women were younger with an average age of 33.8 years compared to 37.4 years in their male counterparts (p=0.002). Women in the seropositive group had a lower body mass index (BMI), averaging 26.2 versus 28.1 in men (p=0.028). Concurrent autoimmune diseases were documented in 36 of the females and 25 of the males (females 20.6%; males 24.8%; p=0.42). Depression was recorded at a high rate in seropositive males and females with a female predominance (females 27.7%; males 9.8%, p=0.0004). Decreased bone mineral density (osteopenia or osteoporosis) rates were low in this group aged 49 years or less (females 0.6%; males 2%, p=0.36). Median follow up time was 6.73 years (95% CI 6.44, 6.93). CONCLUSIONS: Celiac disease is common. The finding of high seropositivity emphasizes the importance of testing patients when there is clinical suspicion for disease. These results indicate the potential of gender-based differences in terms of age at diagnosis, anthropometric measurements, and associated diseases that can co-occur with celiac disease. These findings may be clinically relevant for uncovering cases of celiac disease in the community and once identified, managing them comprehensively. FUNDING AGENCIES: None